Transcript profiling of common bean nodules subjected to oxidative stress. Issue 3 (28th March 2013) - Ramírez, Mario; Guillén, Gabriel; Fuentes, Sara I.; Íñiguez, Luis P.; Aparicio‐Fabre, Rosaura; Zamorano‐Sánchez, David; Encarnación‐Guevara, Sergio; Panzeri, Dario; Castiglioni, Bianca; Cremonesi, Paola; Strozzi, Francesco; Stella, Alessandra; et al.
<x xml:space="preserve">Abstract</x> Several environmental stresses generate high amounts of reactive oxygen species (ROS) in plant cells, resulting in oxidative stress. Symbiotic nitrogen fixation (SNF) in the legume–rhizobia symbiosis is sensitive to damage from oxidative stress. Active nodules of the common bean (Phaseolus vulgaris) exposed to the herbicide paraquat (1, 1′‐dimethyl‐4, 4′‐bipyridinium dichloride hydrate), which stimulates ROS accumulation, exhibited reduced nitrogenase activity and ureide content. We analyzed the global gene response of nodules subjected to oxidative stress using the Bean Custom Array 90K, which includes probes from 30 000 expressed sequence tags (ESTs). A total of 4280 ESTs were differentially expressed in stressed bean nodules; of these, 2218 were repressed. Based on Gene Ontology analysis, these genes were grouped into 42 different biological process categories. Analysis with the PathExpress bioinformatic tool, adapted for bean, identified five significantly repressed metabolic pathways related to carbon/nitrogen metabolism, which is crucial for nodule function. Quantitative reverse transcription (qRT)‐PCR analysis of transcription factor (TF) gene expression showed that 67 TF genes were differentially expressed in nodules exposed to oxidative stress. Putative cis‐elements recognized by highly responsive TF were detected in promoter regions of oxidative stress regulated genes. The expression of oxidative stress responsive genes and of genes important for SNF in bacteroids analyzed in stressed nodules revealed that these conditions elicited a transcriptional response.